Prevalence of periodontitis in patients with type 2 diabetes and its association with metabolic control. Cross-sectional study. Cuenca-Ecuador (Research, Society and Development, 2022)
Objective: to determine the prevalence of periodontitis in patients with type 2 diabetes and its association with metabolic control in patients who received medical care in two foundations in the city of Cuenca - Ecuador during the period of January-April 2015. Methodology: cross-sectional, descriptive-analytical study carried out with 95 patients with type 2 diabetes who were evaluated periodontally and in whom the level of metabolic control of diabetes was identified by means of the glycosylated hemoglobin test; in addition, we inquired about sex, age, duration of diabetes, time elapsed since their last medical check-up. Results: 86.32% of patients with periodontitis were identified, the majority of patients with type 2 diabetes had poor metabolic control (87.36%). A statistically significant association was found between the presence of periodontitis and the degree of metabolic control of diabetes (p=0.003), patients with poorly controlled diabetes (HbA1c ≥ 7.0%) presented a higher risk of presenting periodontitis (OR: 6.67; 95% CI: 1.72-26.08); likewise, a statistically significant association was found between the presence of periodontitis and the duration of diabetes (p=0.013), with a higher risk for patients who have had type 2 diabetes for 10 years or more (OR: 6.064; 95% CI: 1.26-29.08). Conclusion: the prevalence of periodontitis in patients with type 2 diabetes was 86.32%; associations were identified both with poor metabolic control of diabetes (HbA1c ≥ 7.0%) and with type 2 diabetes duration greater than 10 years.